'These Discussions Aren't Happening': Experiences of People Living with Inflammatory Bowel Disease and Talking About Sexual Well-being with Health Care Professionals. (4th March 2021) - Fourie, Simona; Norton, Christine; Jackson, Debra; Czuber-Dochan, Wladyslawa
Abstract: Background: Inflammatory bowel disease [IBD] affects all aspects of life, yet little is known about the impact of the condition on intimacy and sexuality and if such concerns should be discussed with health care professionals. This hermeneutical phenomenological study aimed to explore the experiences of people living with inflammatory bowel disease and discussing their sexuality concerns with health care professionals. Methods: Participants [ n  = 43] aged 17–64 years were recruited. Data were collected via in depth interviews and anonymous narrative accounts [Google Forms]. Thematic analysis was used to analyse the data. Results: An overarching theme 'These discussions aren't happening' with four main themes were generated. The main themes were: 'I can't image talking about sex'; 'I am a person, not my IBD'; 'We need to talk about sex'; and 'Those who talked about sex, talked badly'. Participants described the lack of conversations with their health care professionals on sexual well-being issues, in spite of the importance they gave to the topic, and identified barriers to having such conversations. They made suggestions for future clinical practice that would better meet their needs. The few who had discussed sexual well-being issues with health care professionals reported negative experiences. Conclusions: Patients' needs and preferences, about addressing during clinical appointments concerns related to their sexual well-being, should be addressed routinely and competently by health care professionals. Understanding the implications of inflammatory bowel disease for intimate aspects of the lives of those living with the condition could improve the quality of the care provided.